2014
DOI: 10.1158/2326-6066.cir-13-0123
|View full text |Cite
|
Sign up to set email alerts
|

STING Ligand c-di-GMP Improves Cancer Vaccination against Metastatic Breast Cancer

Abstract: Cancer vaccination may be our best and most benign option for preventing or treating metastatic cancer. However, breakthroughs are hampered by immune suppression in the tumor microenvironment (TME). In this study, we analyzed whether cyclic di-guanylate (c-di-GMP), a ligand for stimulator of interferon genes (STING), could overcome immune suppression and improve vaccination against metastatic breast cancer. Mice with metastatic breast cancer (4T1 model) were therapeutically immunized with an attenuated Listeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 31 publications
4
157
2
Order By: Relevance
“…Although the results of this study imply that the c-di-GMP produced from adenovirus vectors may not enhance vaccines that rely on antibody production, such as those targeting bacterial toxins, the Ad5-VCA0956-stimulated c-di-GMP innate immune response might enhance protection of vaccines that drive cell-mediated immunity such as those targeting viral infections or cancers. Consistent with this idea, c-di-GMP has been shown to exhibit anticancer properties in a number of studies (20,64,65), which are thought to be mediated through stimulation of a type I interferon response as observed here. Miyabe et al (20) showed that enhancing c-di-GMP entry into cancer cells using liposomes increased its efficacy; adenovirus delivery of DGCs to tumors might function similarly by driving synthesis of c-di-GMP in cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…Although the results of this study imply that the c-di-GMP produced from adenovirus vectors may not enhance vaccines that rely on antibody production, such as those targeting bacterial toxins, the Ad5-VCA0956-stimulated c-di-GMP innate immune response might enhance protection of vaccines that drive cell-mediated immunity such as those targeting viral infections or cancers. Consistent with this idea, c-di-GMP has been shown to exhibit anticancer properties in a number of studies (20,64,65), which are thought to be mediated through stimulation of a type I interferon response as observed here. Miyabe et al (20) showed that enhancing c-di-GMP entry into cancer cells using liposomes increased its efficacy; adenovirus delivery of DGCs to tumors might function similarly by driving synthesis of c-di-GMP in cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…Based on patient's cytokine profile, an optimal adjuvant could be selected for combining with cryoablation. For instance, patients with high IL-6 levels may benefit from cryoablation plus Meriva, while patients with low levels of IL-12 may benefit from cryoablation with cyclic di-guanylate (c-di-GMP) 30 or CpG. 31 During the early stage of cancer development (day 28 after tumor development), we did not find a significant difference between cryoablation plus Meriva or cryoablation alone in our efficacy studies.…”
Section: Discussionmentioning
confidence: 69%
“…STING-activating CDNs may have high translational potential as oncology therapeutics due to their potent antitumor activity as a single agent in aggressive mouse syngeneic tumor models (8,63,(83)(84)(85)(86). Therapeutic antitumor efficacy with CDN-based STING agonists was initially demonstrated with daily i.p.…”
Section: Development Of Human Sting Agonists As Cancer Immunotherapeumentioning
confidence: 99%
“…Therapeutic antitumor efficacy with CDN-based STING agonists was initially demonstrated with daily i.p. injection of cyclic diguanylate (c-di-GMP) in the 4T1 mammary carcinoma model (85). However, c-di-GMP and other bacterial CDNs that have a canonical structure defined by a phosphate bridge with two 3′-5′ linkages to join the two purine nucleotides into a cyclic molecule (3′,3′ CDNs) likely have limited translational value due to an inability to activate all human STING alleles D (51,87).…”
Section: Development Of Human Sting Agonists As Cancer Immunotherapeumentioning
confidence: 99%